The dialogical Self from the viewpoint of hermeneutic phenomenology. (September 2019) - Ginev, Dimitri
This paper aims at rereading some tenets of dialogical Self theory in the perspective of hermeneutic phenomenology. It aims at radicalizing the tendency to the anti-Cartesian interpretation of the Self in this theory. The Self is conceived of in terms of an ecstatic unity of psychic subjectivity (as enabling the choices of possibilities) and trans-subjective configurations of practices. The existential possibilities are addressed as emerging from the appropriation of possibilities generated by configured practices. The Self exists in and through (and not behind) this transformation of trans-subjective possibilities into existential ones. The paper defends the situated transcendence of the Self's existence within practices. This defense provides arguments against any approach assuming the existence of "punctual self". From the viewpoint of hermeneutic phenomenology, the conceptualization of the dialogical Self must avoid any form of essentialism. This conceptualization is also at odds with assuming a kind of "transcendental ego" operating behind the Self's pluralism of I-positions. The view of the Self as existing in and through the ongoing transformation of trans-subjective into existential possibilities admits that from the very outset the formation of the Self's identities is predicated on the ecstatic unity of subjectivity and trans-subjectivity.